Van hoog naar laag: migratie van Myrica gale in het Holoceen - Piet Cleveringa; Hendrik Woldring; Dirk van Smeerdijk (Belgeo)
Already in the Boreal Myrica gale (gale; bog myrtle) formed a part of the vegetation of the Drents-Friese Plateau in the Northern Netherlands. During the Subboreal gale became more important. Due to human activity especially in the borderzones of the rivers and streams which drained the Pleistocene grounds of Friesland and Utrecht, the area of Myrica increased. From these borderzones it moved up very quickly to the peat areas of the coastal zone. Once settled in the bogs gale dominated at some places the vegetation of the coastal plain of Friesland and Noord-Holland. Under watery conditions gale produces macroscopic well recognisable rootlets with verrucous tubers. The presence of the coastal barriers and the dunes in the Western Netherlands gives Myrica the opportunity to be an important element of the peat bogs, till the large-scale land reclamation started (± 800 à 1000 AD). In Friesland Myrica is on the way down already during the Roman period. Salt water and long-term drainage caused by the digging of ditches (land reclamation) resulted in the decrease of the area of Myrica.